Cross community study of mathematics anxiety between the high school students in Illinois USA and Jordan / Ruba Mohammad Miqdadi - Mohammad Miqdadi, Ruba (Research Management Institute (RMI), 2012)
The purpose ofthe study is to examine whether there are any significant differences in the mathematics anxiety levels between high school students in Jordan and their counterparts in the United States. Another purpose is to examine whether there are gender differences related to mathematics anxiety among high school students ofboth communities. A total of 1,386 high school students in the United States and Jordan participated in main study. This study showed that Jordanian high school students exhibited a significantly higher mathematics anxiety than United States high school students. Furthermore, the study revealed that female high schooLstudents in the United States acquired a significantly higher mathematics anxiety level than males. Another finding of this study was that males in Jordan had a significantly higher leveL of mathematics anxiety than males in the United States. The findings and educational implications ofthe study are discussed in light ofthe cultural difference between the two communities.